A facile room temperature solution synthesis of SnO2 quantum dots for perovskite solar cells. Issue 17 (10th April 2019) - Liu, Hongri; Chen, Zhiliang; Wang, Haibing; Ye, Feihong; Ma, Junjie; Zheng, Xiaolu; Gui, Pengbin; Xiong, Liangbin; Wen, Jian; Fang, Guojia
Abstract : We introduce a facile route to synthesize SnO2 quantum dots colloidal solution at room temperature and superior homogeneous ETL is obtained by spin coating of the QDs colloidal solution with post-deposition annealing. Abstract : The electron transport layer (ETL) is a critical component in planar single junction or tandem perovskite solar cells (PSCs), dominating the separation and electron extraction of charge carriers. Herein, we introduce a facile route to synthesize a SnO2 quantum dot (QD) colloidal solution at room temperature using an alcohol-based solvent with the additive of deionized-water. A superior homogeneous ETL is obtained by spin coating of the QD colloidal solution with post-deposition annealing. Compared to the ETL prepared with the SnCl2 ·2H2 O anhydrous alcohol solution, the champion power conversion efficiency of PSCs deposited on the SnO2 QD based ETL is raised to 20.1% from 16.5%. The better performance is attributed to the excellent optical and electronic properties of the SnO2 QD based ETL. Experimental analyses reveal that the SnO2 QD based ETL enhances electron extraction and suppresses charge recombination, leading to improvement of solar cell performance. The appropriate concentration of the SnO2 QD based solution is explored and the appropriate ratio of anhydrous alcohol to deionized water of the SnO2 colloidal solution is obtained. Our results show the great potential of low temperature synthesized SnO2 QD films for application as ETLs or interconnecting buffer layers for future highly efficient and reproducible low-temperature processed tandem PSCs.